Uma análise crítica das relações de serviços educacionais : o caso dos docentes de matemática da Universidade Federal do Espírito Santo - Iwamoto, Helga Midori (2006)
This work had the goal of understanding the dynamics of the services provision inside the Federal University of the state of Espírito Santo (UFES) – Brazil in the case of the mathematics classes lectured to the students from disciplines offered by the Dep